2008
DOI: 10.1159/000157373
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Improves Sleep-Related Breathing in Hemodialysis Patients

Abstract: Aims: To assess whether kidney transplantation improves sleep-related breathing disorders associated with hemodialysis. Methods: A prospective study was carried out using full-night polysomnography. Nine hemodialysis patients (7 men and 2 women, aged 42 ± 16.2 years, BMI 26 ± 3.7) who later received a successful kidney transplantation were evaluated. Main sleep quality and respiratory variables were recorded: number of dips in oxygen saturation (SaO2) ≥3% per hour of sleep; percentage of sleep time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
3
20
1
Order By: Relevance
“…We could find only four studies that have examined the effect of transplant on SDB in patients with ESRD; three of these studies have been carried out using PSG; one each from Canada (n = 18) [16], Spain (n = 9) [18], and Brazil (n = 34) [17], while one has additionally been carried out using portable ventilation recorder in South Korea (n = 20) [19]. Our sample size (n = 18) is similar to the ones in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could find only four studies that have examined the effect of transplant on SDB in patients with ESRD; three of these studies have been carried out using PSG; one each from Canada (n = 18) [16], Spain (n = 9) [18], and Brazil (n = 34) [17], while one has additionally been carried out using portable ventilation recorder in South Korea (n = 20) [19]. Our sample size (n = 18) is similar to the ones in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found the prevalence of Sleep ApneaeHypopnea Syndrome (SAHS) in patients on HD to be 44% [15]. There have been conflicting results regarding the effect of renal transplantation, with two studies [16,17] showing no or minimal improvement in AHI or SDB and two studies showing marked improvement [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Laboratory-assessed PSG studies among the kTx recipient population included much fewer patients (n 1 = 18; n 2 = 9; n 3 = 34, respectively) and mainly focused on sleep apnea and the change of the sleep structure associated with apnea treatment or transplantation. [56][57][58] Although some sleep macrostructure parameters were reported in these studies, little attention was paid to stage 2 sleep or REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…57 REM latency was only reported in one study (133 ± 76 minutes). 57 Interestingly, the proportion of REM sleep was also associated with declining renal function in patients with CKD, however, this association diminished after controlling for covariables. 54 Depressive symptoms were not considered in any of the previously mentioned studies.…”
mentioning
confidence: 84%
“…In addition to the clinical associations with these sleep disorders, advanced CKD has been linked to the suppression of the melatonin surge that is integrally linked to the regulation of the circadian rhythm [32,33]. Further evidence that advanced CKD exacerbates sleep disturbance is the observation that kidney transplantation and long nocturnal hemodialysis partially correct sleep apnea in dialysis patients [34,35,36]. …”
Section: Discussionmentioning
confidence: 99%